Asuhan Kebidanan Komprehensif Pada Ny.E Umur 39 Tahun G3P1A1 Dengan Faktor Resiko Umur, Kek Dan Anemia di BPM Ny.R Wilayah Kerja Puskesmas Bumiayu Tahun 2023 - Nadia Eka Khaerunnisa; Endang Susilowati; Riyanti Riyanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
According to WHO (2019), the maternal mortality rate (MMR) in the world is 303,000 people. The Maternal Mortality Rate (MMR) in ASEAN (2020) is 235/100,000 live births. Based on data from the Ministry of Health, the Maternal Mortality Rate (MMR) in Indonesia in 2020 was 4,627 deaths. Health Department data (2021) MMR 62 cases. Data from Bumiayu Community Health Center (2022) AKI 2 cases. The aim of this research is to reduce maternal and infant morbidity and mortality rates in Brebes Regency, especially the Bumiayu Community Health Center area. This research method uses descriptive research with a qualitative descriptive approach. The results of this research show that in the results of Comprehensive Care there was a gap between theory and practice after comprehensive midwifery care was carried out on Mrs. E is 39 years old with risk factors for CED age and anemia in Mrs. BPM. R working area of Bumiayu Health Center from third trimester pregnancy, childbirth, newborns, postpartum and family planning using Varney midwifery and SOAP approaches.